Improving Schools in Difficulty - Clarke,Paul; Paul Clarke (London Continumm, 2006)
Improving schools in difficulty is structured around two parts;part one examines the principles of engagement with schools in difficulty and part two looks at ways of improving the process of supporting schools in difficulty .What we say collectively in this book suggests that a new line of interpretation of challenge is emerging which is far more critical of the existing arrangements we take a view of improvement which is more deeply rooted in the emancipatory potential of education as a vehicle for social change.Our views are not imperical or simply theoritical,they are rooted in practice and arise from observation of practice and make a call for more radical solutions to be exercised.
Includes index
Keywords: Educational Resources